Development of Website-Based Thousand Island Tour Package Booking Application Using Waterfall Method - Nurhaliza Nurhaliza; Nurullah Husufa (Journal of Information System and Informatics, 2022)
PT. Khatulistiwa Global Wisata is a company engaged in tourism and offers a Tour and Travel service called Explore Thousand Islands. Currently, the process of booking Pulau Seribu tour packages at Explore Seribu Pulau Tour and Travel is still done manually, causing visitor data, bookings, payments, and visitor reviews to not be recorded properly. This website-based thousand island tour package online booking application is designed using the Waterfall method, CodeIgniter as a framework, PHP for designing the web, and MySQL as a database storage. Research has been conducted to overcome problems by creating features such as tour package list features, tour package bookings, tour package payments, manage payments, approve payments, manage assignment trips, complete trip assignments, and give trip reviews. The features developed make it easier for visitors to find information on tour packages, book, pay, and review tour trips that have been carried out. In addition, the existence of the report feature can improve performance and make it easier for tourism agents to record reports from booking thousand island tour packages through the website.